Procarcinogenic regulatory T cells in microbial-induced colon cancer. (2nd April 2016) - Geis, Abby L.; Housseau, Franck
ABSTRACT: Regulatory T cell (Treg) promote IL-17-mediated colon tumorigenesis in multiple intestinal neoplasia (Min) mice colonized with enterotoxigenic Bacteroides fragilis (ETBF). Although they retain their immunosuppressive function, mucosal Treg are instrumental to initiate ETBF-triggered IL-17 colitis by limiting the availability of IL-2 in the local microenvironment. However, the mechanisms that trigger the recruitment of the pro-carcinogenic Treg in ETBF-colonized colon remained to be elucidated.